2007
DOI: 10.1002/bdm.570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prior interpretation on situation assessment in crime analysis

Abstract: A main threat to objective information processing in crime investigation teams is the tendency to focus on one particular interpretation only. To prevent such tunnel vision or 'groupthink', an investigation team can call in a crime analyst, and ask him or her to give a fresh and independent account of the evidence at hand. However, before they examine the case, crime analysts are often already aware of the scenario currently favoured by the team. In our experiment, we investigated whether such prior knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Meanwhile, the fi ndings cast some doubt on the assumption that the confi rmation bias lurks in legal decision making (see Kerstholt & Eikelboom, 2007;Schünemann & Bandilla, 1989). That is, leaving one exception, it can be concluded that participants did not favour incriminating evidence over exonerating evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the fi ndings cast some doubt on the assumption that the confi rmation bias lurks in legal decision making (see Kerstholt & Eikelboom, 2007;Schünemann & Bandilla, 1989). That is, leaving one exception, it can be concluded that participants did not favour incriminating evidence over exonerating evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies with law enforcement personnel (Ask & Granhag 2007b;Ask et al 2008;Charman et al 2017;Ditrich 2015;Groenendaal & Helsloot 2015;Marksteiner et al 2010;Rassin 2010;Wallace 2015) examined aspects of confirmation bias; one addressed the distinct but related phenomenon of groupthink (Kerstholt & Eikelboom 2007). The importance of this issue was demonstrated by a survey of an unspecified number of professional crime scene officers conducted by Ditrich (2015), asking for their opinions about the relative frequency and severity of various cognitive errors that could potentially negatively affect a criminal investigation; based on their experiences, respondents highlighted confirmation bias (as well as overestimating the validity of partial information and shifting the burden of proof to the suspect).…”
Section: Human Naturementioning
confidence: 99%
“…What alternative scenario can then be employed to remain open minded? Kerstholt and Eikelboom (2007) found that even professional crime analysists sometimes experience difficulties in producing alternative scenarios. But even if an alternative scenario is present, it is unclear how the alternative should be used (Mynatt, Doherty, & Dragan, 1993).…”
mentioning
confidence: 99%